Encyclopedia of signaling molecules - Chio, Shangdun (Springer New York, 2012)
Biological processes are driven by complex systems of functionally interacting signaling molecules. Thus, understanding signaling molecules is essential to explain normal or pathological biological phenomena. A large body of clinical and experimental data has been accumulated over these years, albeit in fragmented state. Hence, systems biological approaches concomitant with the understanding of each molecule are ideal to delineate signaling networks/pathways involved in the biologically important processes. The control of these signaling pathways will enrich our healthier life. Currently, there are more than 30,000 genes in human genome. However, not all the proteins encoded by these genes work equally in order to maintain homeostasis. Understanding the important signaling molecules as completely as possible will significantly improve our research-based teaching and scientific capabilities. This encyclopedia presents 350 biologically important signaling molecules and the content is built on the core concepts of their functions along with early findings written by some of the world's foremost experts. The molecules are described by recognized leaders in each molecule. The interactions of these single molecules in signal transduction networks will also be explored. This encyclopedia marks a new era in overview of current cellular signaling molecules for the specialist and the interested non-specialist alike During past years, there were multiple databases to gather this information briefly and very partially. Amidst the excitement of these findings, one of the great scientific tasks of the coming century is to bring all the useful information into a place. Such an approach is arduous but at the end will infuse the lacunas and considerably be a streamline in the understanding of vibrant signaling networks. Based on this easy-approach, we can build up more complicated biological systems.